2012
DOI: 10.1111/j.1471-4159.2012.07680.x
|View full text |Cite
|
Sign up to set email alerts
|

A G‐Rich element forms a G‐quadruplex and regulates BACE1 mRNA alternative splicing

Abstract: β-site APP cleaving enzyme 1 (BACE1) is the transmembrane aspartyl protease that catalyzes the first cleavage step in the proteolysis of the amyloid β-protein precursor (APP) to the amyloid β-protein (Aβ), a process involved in the pathogenesis of Alzheimer disease. BACE1 pre-mRNA undergoes complex alternative splicing, the regulation of which is not well understood. We identified a G-rich sequence within exon 3 of BACE1 involved in controlling splice site selection. Mutation of the G-rich sequence decreased u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 29 publications
2
84
1
Order By: Relevance
“…Although preliminary, these results suggest that the expanded (GGGGCC) n repeat may potentially autoregulate C9orf72 splicing (4). Our observation that the r(GGGGCC) n repeat can assume a G-quadruplex opens the question as to whether such structures may affect C9orf72 splicing outcomes, as occurs for other genes (33,42). We found that the splicing regulator ASF/ SF2 bound in vitro to the C9orf72 repeat, as predicted based on sequence specificity (34).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Although preliminary, these results suggest that the expanded (GGGGCC) n repeat may potentially autoregulate C9orf72 splicing (4). Our observation that the r(GGGGCC) n repeat can assume a G-quadruplex opens the question as to whether such structures may affect C9orf72 splicing outcomes, as occurs for other genes (33,42). We found that the splicing regulator ASF/ SF2 bound in vitro to the C9orf72 repeat, as predicted based on sequence specificity (34).…”
Section: Discussionmentioning
confidence: 53%
“…Gquadruplexes can affect alternative splicing (33,42). The (GGGGCC) n repeat lies within the noncoding region of the C9orf72 gene, which can be alternatively spliced to three isoforms (3,4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Formation and stability of these RNA structures is dependent on the presence of different ions under in vitro conditions. 4-8 Functionally, RNA G-quadruplexes act as modulators of gene expression and have been shown to regulate a number of processes such as mRNA translation, 9-12 telomere biology, 13 mRNA localisation, 14 pre-mRNA splicing 15 to name a few. Absence of complementary strand for RNA makes it more amenable to form secondary structures in comparison to duplex DNA.…”
mentioning
confidence: 99%
“…[3][4][5] Furthermore, GQs hold regulative potential for gene expression either on the transcriptional level by being part of or close to promoters in genomic DNA (e.g. c-MYC or bcl2 promoter) 6,7 or as regulators of splicing 8 and translation 9 (inhibitory or enhancing) when present in mRNAs and finally as regulative elements by binding of certain effector proteins. 3,10 It has been shown that due to this fact GQs are also crucial elements in the development or progression of malignancy such as neurodegenerative disorders 11 and cancer.…”
Section: Introductionmentioning
confidence: 99%